ibM Kelompok Tani Jamur Tiram di Kelurahan Tlogomulyo - Fatmasari Sukesti; Setia Iriyanto; Purnomo Purnomo (MAKSIMUM, 2014)
Oyster mushrooms easily to cultivated so this activities become to choice of small and medium enterprises (SMEs) to conduct cultivation. Oyster mushroom (Pleurotus ostreatus) is a nutritious food ingredients with high protein, rich in vitamins and minerals, low in carbohydrates, fat and calories. Oyster mushroom products can not only be consumed in the form of cooked vagetables, but can be processes into a form processed foods like crispy mushrooms, mushroom chips, nuggets mushroom, mushroom dumplings, and other processed foods. Farmer groups "Agro Mandiri Graha" develop the cultivation of oyster mushroom by processing into food products. With the ibM program the persons from Unimus team partnered with farmer groups "Agro Mandiri Graha" to enhance the ability of members of the group in the development of agribusiness and the strengthening of farmer group became strong farmers organizations and independent. The result obtained from ibM are : improved the skills of farmers cultivate oyster mushrooms in oyster mushroom into food products like : mushroom chips, nuggets mushroom, mushroom dumplings, meatballs mushrooms, mushroom satay and crispy mushrooms and improve financial management and marketing of productsKeyword : oyster mushrooma, processed foods, agribusiness development